The ultra-small strongest grain size in nanocrystalline Ni nanowires. (1st January 2015) - Cao, Ronggen; Deng, Chuang
Abstract : Here we report the finding that the strongest grain size to achieve the maximum flow stress in nanocrystalline Ni nanowires was significantly smaller (d = 5 nm) than that in typical bulk metals (d > 10 nm). The discrepancy was due to the dominance of plasticity via surface slip in Ni nanowires at relatively large grain sizes, which was absent in bulk materials. An interesting grain size- and temperature-dependent "hardening"-to-"softening" transition in Ni nanowires was also revealed in this study.